Sharing the Role of Peace - Andry Fitriyanto (Al-Albab, 2017)
Eka Hendry Ar., Sharing the Role of Peace. Pontianak: IAIN Pontianak Press, 2016 The tragedy of Habil’s death in the hands of Qabil shows that from the very beginning of human life on earth, it has been filled by conflict. It is a necessity in our lives. Just like crime and good, peace and conflict are also two things that continue to fill the human life. Then, can we materialize true peace where there is no conflict in it? This book, Sharing Role of Peace begins with a very philosophical study. It is like inviting the reader to reflect again on the meaning of peace and conflict. Both are a paradox. In contrast to each other, but they need each other. Conflict is caused by the realization of a peace which requires the non-existence of conflict. If there is a conflict, then peace will be gone. But on the other hand, they also need each other. Peace requires conflict as a driver of change for the better. Conflict requires peace as the ultimate goal.